Early T Stage Is Associated With Poor Prognosis in Patients With Metastatic Liver Colorectal Cancer - Wu, Lunpo; Fu, Jianfei; Chen, Yi; Wang, Liangjing; Zheng, Shu (Frontiers in Oncology, 2020)
Clinically, a considerable portion of patients with early T stage who were supposed to have a low distant metastatic probability, were diagnosed with metastatic liver colorectal cancer (CRLM). Our study aims to evaluate the prognostic value of the T stage for metastatic patients and establish a convenient individual assessment model for clinicians to explore preoperative predictors. The mRNA profiles of colorectal tumors (N=19) were obtained by microarray at our clinical center. A total of 5,618 patients with CRLM from 2010 to 2015 were enrolled for the Surveillance, Epidemiology, and End Results (SEER) database. The cDNA microarray analyses showed that gene expression pattern in the T2N0M1 subgroup was significantly different from the T3/4N0M0 subgroup. In the survival analysis, metastatic patients with T1 stage surprisingly had much poorer prognosis than those with T3/T4 stage. Specifically, metastatic patients with early T stage were observed with higher frequency occurring at the rectum, better differentiation, less metastases in the lymph nodes, and a higher CEA level. Further survival analysis indicated that early T classification was an independent prognostic factor for a poor survival. When the lymph node (N) status was taken into consideration, patients with T1/2N+ had better survival than T1/2N0 patients. A clinical nomogram was constructed based on preoperative factors. The calibration curves showed a good concordance between nomogram prediction and actual observation. In conclusion, CRLM with early T stage had a different biological background. The prognosis of patients at T1/2M1 was poorer than at T3/4M1. More attention should be paid to the surveillance of high-risk factors and the screening of early T stage.